Gemcitabine-Based Neoadjuvant Treatment in Borderline Resectable Pancreatic Ductal Adenocarcinoma: A Meta-Analysis of Individual Patient Data - Giovinazzo, Francesco; Soggiu, Fiammetta; Jang, Jin-Young; Versteijne, Eva; van Tienhoven, Geertjan; van Eijck, Casper H.; Han, Youngmin; Choi, Seong Ho; Kang, Chang Moo; Zalupski, Mark; Ahmad, Hasham; Yentz, Sarah; et al. (Frontiers in Oncology, 2020)
Background: Non-randomized studies have investigated multi-agent gemcitabine-based neo-adjuvant therapies (GEM-NAT) in borderline resectable pancreatic ductal adenocarcinoma (BR-PDAC). Treatment sequencing and specific elements of neoadjuvant treatment are still under investigation. The present meta-analysis aims to assess the effectiveness of GEM-NAT on overall survival (OS) in BR-PDAC. Patients and Methods: A meta-analysis of individual participant data (IPD) on GEM-NAT for BR-PDAC were performed. The primary outcome was OS after treatment with GEM-based chemotherapy. In the Individual Patient Data analysis data were reappraised and confirmed as BR-PDAC on provided radiological data. Results: Six studies investigating GEM-NAT were included in the IPD metanalysis. The IPD metanalysis was conducted on 271 patients who received GEM-NAT. Pooled median patient-level OS was 22.2 months (95%CI 19.1–25.2). R0 rates ranged between 81 and 95% (I2 = 0%, p = 0.64), respectively. Median OS was 27.8 months (95%CI 23.9–31.6) in the patients who received NAT-GEM followed by resection compared to 15.4 months (95%CI 12.3–18.4) for NAT-GEM without resection and 13.0 months (95%CI 7.4–18.5) in the group of patients who received upfront surgery (p < 0.0001). R0 rates ranged between 81 and 95% (I2 = 0%, p = 0.64), respectively. Overall survival in the R0 group was 29.3 months (95% CI 24.3–34.2) vs. 16.2 months (95% CI 7·9–24.5) in the R1 group (p = 0·001). Conclusions: The present study is the first meta-analysis combining IPD from a number of international centers with BR-PDAC in a cohort that underwent multi-agent gemcitabine neoadjuvant therapy (GEM-NAT) before surgery. GEM-NAT followed by surgical resection improve survival and R0 resection in BR-PDAC. Also, GEM-NAT may result in a good palliative option in non-resected patients because of progressive disease after neoadjuvant treatment. Results from randomized controlled trials (RCTs) are awaited to validate these findings.